Adult interdisciplinary therapy - Bala Krishnan Rajkumar; Padmanaban Janarthanam (Wolters Kluwer Medknow Publications, 2012)
Adult patients have many preexisting conditions like tooth loss, severe skeletal dysplasia, periodontal disease, and various temporomandibular dysfunctions. In such adult patients, an interdisciplinary treatment approach is followed by customizing orthodontic treatment for the individual patient. This article shows a case that is managed in an interdisciplinary method of treatment approach.